SISTEM PERHITUNGAN HARGA POKOK PENJUALAN MELALUI PENDEKATAN FIRST IN FIRST OUT - Fidya Arie Pratama (Jurnal Digit, 2018)
Abstract Companies often have difficulty in calculating cost of goods sold. There are some companies still use microsoft excel and the absence of the cost of sales approach approach. Affects the price of the product, the company's final report that determines the loss or profit in the company. One approach used in recording the cost of goods sold is the FIFO (First In First Out) approach. While the system development approach is using System Development Life Cycle (SDLC) with Waterfall model. The programming languages used are PHP, MySQL database, Localhost XAMPP, Notepad ++ editor, and data obtained from data collection at PT. Herbatama Indo Perkasa Cirebon City. The results of this paper is to design a running system, build a new system, and implement the system terebut with black box testing. So as to produce a computerized system and able to solve the problem of cost of goods sold. Keywords: First In First Out, Cost of Goods Sold, Accounting Information System